A fascinating multitasking Cu-MOF/rGO hybrid for high performance supercapacitors and highly sensitive and selective electrochemical nitrite sensors. Issue 42 (6th October 2016) - Saraf, Mohit; Rajak, Richa; Mobin, Shaikh M.
Abstract : A hybrid (Cu-MOF/rGO) prepared by sonication mixing of a Cu-MOF and rGO shows high potential for both supercapacitors and nitrite sensors. Abstract : Herein, we report a multitasking Cu-MOF/rGO hybrid, fabricated by simple ultra-sonication of slow diffusion driven Cu-MOF crystals with chemically synthesized reduced graphene oxide (rGO). The molecular structure of the Cu-MOF was authenticated by single crystal X-ray studies. The prepared materials have been probed by various physicochemical characterization techniques. Due to the positive synergistic effects between Cu-MOF crystals and rGO nanosheets, the newly synthesized Cu-MOF/rGO hybrid delivers high charge storage efficiency (685.33 F g −1 at 1.6 A g −1 ), high energy (137.066 W h kg −1 ) and power density (4800.04 W kg −1 ) and excellent rate ability (retains 71.01% of its initial capacitance at 8 A g −1 ). Furthermore, the long cycle life (91.91% after 1000 cycles) of this hybrid indicates its high stability on the electrode surface. Additionally, the electrode modified with the Cu-MOF/rGO hybrid performs exceptionally towards the electrochemical detection of nitrite in a wide dynamic linear range of 3–40 000 μM ( R 2 = 0.99911), with a notable detection limit of 33 nm and a high sensitivity of 43.736 μA μM −1 cm −2 . The versatility of the Cu-MOF/rGO modified electrode can be observed by distinguished selectivity in the presence of some common interfering species and also ability to detect nitrite in real samples.